Orto, Ocaso y Resurrección de los Centros Históricos en México - Chanes Nieto, José (Acta Universitaria, 2001)
Historic centers, departure and return points, memory and invention of a future, are places of roots, life and history. Technical development and a desire for profit, substitutes for religion and culture, open up new ways to transform and even annihilate these traditional centers of artistic splendor. Pollution, mercantilism, negligence, authorities and landlord’s irresponsability are the enemies of historic centers. Revaluing historic centers requires help from both government and society. Death of the mexican greatness shall be the death of our identify. A nation with no cultural heritage is meant to perish.